The level of public servants’ ethics and their performance : A case study of Immigration Department of Melaka / Fatin Syuhada Yahaya and Nur Qhaleda Rohaizat - Yahaya, Fatin Syuhada; Rohaizat, Nur Qhaleda (Faculty of Administrative Science and Policy Studies, 2014)
“The Malayan Civil Service (MCS) is now known as the Malaysian Public Service, inherited its legacy from the British Public Service with significant fundamental changes taking place over the last 50 years” (Office of the Chief Secretary to the Government, 2013). The pursuit of effective public sector administration can be explained as a series of ideas, each representing a step, or increment, towards a complete theory of public administration. Daniel (1994) stated that they have assisted build an extensive tank of knowledge and public administration is a matter of human inquisition with ancient roots. Public administration is often characterized as an application of social and other sciences to public problems, thus bridging disciplines (Frederickson, 1976). He also said that public servants hired based on their expertise and oriented in the career service to be neutral politically and possess detailed knowledge of management techniques and practices as well as they serve for the public.